Penerapan Analisis Faktor Eksplanatori pada Pengambilan Keputusan Mahasiswa Membeli Produk Online di Kota Makassar - Ihsan, Hisyam; Wahyuni, Maya Sari; Kurnadipare, Aleytha Ilahnugrah (Jurusan Matematika FMIPA UNM, 2023)
Abstract. This research is applied research using exploratory factor analysis in the decision making of students buying online products in Makassar City. The data collection method used was a survey through a questionnaire. There are 8 explanatory variables or factors that are the focus of the research, each consisting of 4 indicators with a total of 240 respondents. Tests were performed using KMO, Bartlett and MSA tests, as well as confirmation of eigenvalues greater than 1 and based on emerging loading factors, 8 factors influence student decision making to buy online products, namely customer review factors, process factors and free shipping costs, influencer marketing factors, price factors, distribution factors, promotion factors, product factors, and shopping terms factors.